Reconstructing the evolutionary history of F420-dependent dehydrogenases - Mascotti, María Laura (2018)
During the last decade the number of characterized F420-dependent enzymes has significantly increased. Many of these deazaflavoproteins share a TIM-barrel fold and are structurally related to FMN-dependent luciferases and monooxygenases. In this work, we traced the origin and evolutionary history of the F420-dependent enzymes within the luciferase-like superfamily. By a thorough phylogenetic analysis we inferred that the F420-dependent enzymes emerged from a FMN-dependent common ancestor. Furthermore, the data show that during evolution, the family of deazaflavoproteins split into two well-defined groups of enzymes: the F420-dependent dehydrogenases and the F420-dependent reductases. By such event, the dehydrogenases specialized in generating the reduced deazaflavin cofactor, while the reductases employ the reduced F420 for catalysis. Particularly, we focused on investigating the dehydrogenase subfamily and demonstrated that this group diversified into three types of dehydrogenases: the already known F420-dependent glucose-6-phosphate dehydrogenases, the F420-dependent alcohol dehydrogenases, and the sugar-6-phosphate dehydrogenases that were identified in this study. By reconstructing and experimentally characterizing ancestral and extant representatives of F420-dependent dehydrogenases, their biochemical properties were investigated and compared. We propose an evolutionary path for the emergence and diversification of the TIM-barrel fold F420-dependent dehydrogenases subfamily.